PENGARUH ILMU AKUNTANSI DAN MINAT PENCATATAN AKUNTANSI TERHADAP KEBERHASILAN USAHA MIKRO DI KABUPATEN KARANGANYAR - Anindita Triasanti; Rispantyo Rispantyo; Djoko Kristianto (Universitas Slamet Riyadi, 2020)
Micro Business has a very important role for financial development in certain areas. The purposenofnthisnstudynwasntonanalyzenthensignificancenof the influencenofnaccounting science andnaccounting record interest in the success of microbusinesses innKaranganyarnRegency. Thenpopulationnofnthisnresearchnis all business operators in Karanganyar Regency, amounting to 46,000 micro businesses, while the sample ofnthisnstudynisn100nbusinessnoperators. The researchnmethod uses dmultiple nlinearn regressionn analysisn methods. Thenresults showed simultaneously that accounting sciencenvariablesnand accounting record interestsnhadnanpositivenandnsignificantneffectnonnthensuccessnofnmicrobusinesss innKaranganyar Regency.